FORMATION OF SCHOOLCHILDREN'S COGNITIVE INTEREST IN LEARNING IN THE LESSONS FROM ART CULTURE (Pedagogy of Higher and Secondary Education, 2022)
In the article the concept "cognitive concern" is esteemed and its levels are investigated. The conditions of increase of a level of cognitive concern learning on lessons of the world art culture with usage of synthesis o f arts are designed.